1992
DOI: 10.1108/08876049210035944
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Product and Services Television Commercials

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm: 463575 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 0 publications
2
51
0
Order By: Relevance
“…In her words, "Goods and services require distinct advertising strategies" (Sta¬ord, 1996, p. 23). Murray and Schlacter (1990), Stern (1988) and Zinkhan, Johnson, and Zinkhan (1992) con¼rm this. Cutler and Javalgi have found that service advertisements more often contain an emotional appeal (metaphor, storytelling, or aesthetic) than do product advertisements (Cutler and Javalgi, 1993).…”
Section: Validitymentioning
confidence: 81%
“…In her words, "Goods and services require distinct advertising strategies" (Sta¬ord, 1996, p. 23). Murray and Schlacter (1990), Stern (1988) and Zinkhan, Johnson, and Zinkhan (1992) con¼rm this. Cutler and Javalgi have found that service advertisements more often contain an emotional appeal (metaphor, storytelling, or aesthetic) than do product advertisements (Cutler and Javalgi, 1993).…”
Section: Validitymentioning
confidence: 81%
“…Early research on message strategies and tactics was either conceptual (e.g., George and Berry 1981;Legg and Baker 1987) or limited to content analysis (e.g., Cutler and Javalgi 1993;LaBand, Pickett, and Grove 1992;Zinkhan, Johnson, and Zinkhan 1992). LaBand, Pickett, and Grove (1992) and Zinkhan, Johnson, and Zinkhan (1992) found that services advertisers used more informational or cognitive ads; in contrast, Cutler and Javalgi (1993) reported the use of more emotional appeals.…”
Section: Intersection 3: Services Advertising (Sa)mentioning
confidence: 94%
“…Because of these well-accepted differences, effective advertising strategies for goods cannot be automatically applied to services (cf. Zeithaml, Parasuraman, and Berry 1985;Zinkhan, Johnson, and Zinkhan 1992). Therefore, the unique attributes of services, combined with the inherent differences across cultures, present specific challenges for international service providers.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Yet, other scholars suggest that appeals generating an emotional response will induce more positive reactions (Goldberg and Gorn, 1987), and higher levels of recall (Choi and Thorson, 1983). In the service industry, there is evidence that informational or cognitive advertising is more frequently used by firms (Zinkhan, Johnson and Zinkhan, 1992), and is superior to emotional appeals (Stafford and Day, 1995). This is because rational and informative appeals may help reduce some of the uncertainty often associated with the purchase of services.…”
Section: Advertising Strategymentioning
confidence: 99%